A Position Analysis of BPJS Claims Administration Officers and Verifiers (Case Study: Jambi Province Regional Mental Hospital) - Hanisah, Hanisah; Ainy, Asmaripa; Budi, Iwan Stia (Universitas Negeri Malang, 2023)
The high coverage rate of handling partially rejected claim financing reaching 7.34% of the total 19,476 cases in the Outpatient Unit of the Jambi Provincial Mental Hospital (RSJD) in 2022, is closely related to the quality of human resources (HR) in this case, the claims officer and the suitability of what is done with the job description, job specifications and standard operating procedures (SOP) that have been made. This study aimed to analyze the position of administrative officers and claim verifiers in the outpatient unit of the Jambi Provincial Mental Hospital. This research used a qualitative method. Information was collected through in-depth interviews with eight informants, observation, and document review. Test validity by triangulating sources, techniques, and data. The results showed that officers already knew the claims administration and verification procedures. The claim administration SOP in this case, the RJTL claim submission SOP and the monthly reporting SOP have not been outlined in a decision letter for the coding SOP. However, it has been outlined in a decision letter but has not been adequately socialized to the officers concerned. The SOP for claim verification has not been outlined in a decision letter and still refers to the technical guidelines for claim verification issued by BPJS Health. It is still found that the delegation of tasks and the number of verification officers not following the calculation of workload and standards set are obstacles in implementing administration and verification of claims in the Jambi Province RSJD outpatient department.